Research on Design and Development of Elder-Friendly Furniture in Chinese Residential Situation - Junli, Zhang; Musdi, Shanat (Paradigm Academic Press, 2023)
Purpose: In order to actively respond to the social pressure brought by the aging of the population in China, torespond to the smooth operation of the national “multi-level elderly care service systembased on home, supported by community and supplemented by institutions”, to help the elderly with declining physical andmental functions to adapt to current living environment, to extend their time of independent and safe life. Methodology: Based on characteristics of China’s aging situation and the current market of elderly-friendlyfurniture in China, the article started from the characteristics, behavioral habits and demands of the elderly, Conclusion: Proposed design ideas and development strategies of elderly-friendly furniture in residential situation, including elderly-friendly design methods for basic furniture such as sitting and lying furniture, storageand operation furniture, as well as emotional, applicable and standardized development strategies. It is suggestedthat the furniture categories should be refined when the market is mature, so as to activate the elderly-friendlyfurniture market and promote it step by step, and guide the steady development of the furniture industry